2016
DOI: 10.4209/aaqr.2015.04.0256
|View full text |Cite
|
Sign up to set email alerts
|

Water-Soluble Organic Nitrogen in High Mountain Snow Samples from Central Japan

Abstract: We measured water-soluble organic nitrogen (WSON) in snow pit samples, which were collected at the Murodo-Daira snowfield near the summit of Mt. Tateyama, central Japan in 2008. The concentrations of WSON ranged from 12.8 to 96.7 ng g -1 , which were significantly lower than those reported in continental wet deposition samples from the Asian continent. WSON may be largely diluted in the snow samples during snowing processes over the high mountains. We found that WSON significantly correlated with nss-Ca 2+ and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Asian dust is a significant source of atmospheric water‐soluble organic nitrogen (WSON) [ Shi et al ., ; Mochizuki et al ., ]. In a previous study, we observed a moderately significant linear correlation between WSON and nss‐Ca 2+ in the snowpack samples from Mount Tateyama in spring 2009 and 2011 [ Mochizuki et al ., ], suggesting their probable source from Asian dust.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Asian dust is a significant source of atmospheric water‐soluble organic nitrogen (WSON) [ Shi et al ., ; Mochizuki et al ., ]. In a previous study, we observed a moderately significant linear correlation between WSON and nss‐Ca 2+ in the snowpack samples from Mount Tateyama in spring 2009 and 2011 [ Mochizuki et al ., ], suggesting their probable source from Asian dust.…”
Section: Resultsmentioning
confidence: 99%
“…On 18 April 2009 and 17 April 2011, two snow pit holes were dug to the depth of 6.0 and 6.5 m, respectively, and snowpack samples were collected using a precleaned shovel to avoid possible contamination. We found dust‐containing snow layers in the snow pits; they showed a light yellow‐brown color and were later characterized by high Ca 2+ concentrations, suggesting long‐range transport of Asian dust to the sampling site [ Mochizuki et al ., ]. Previous studies [ Kawamura et al ., ; Maki et al ., ; Osada et al ., ; Tanaka et al ., ] also suggested that snow samples collected from the same site are influenced by Asian dust.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The details on the snow collection and sample storage methods were described in Kawamura et al (2012) and Mochizuki et al (2016). Snowpack samples were collected at the Murodo-Daira site (36.58 • N, 137.36 • E; elevation 2450 m) near Mt.…”
Section: Sample Collectionmentioning
confidence: 99%
“…Their results suggest that bacterial ice nuclei are present in the rainwater but play a minor role in ice nucleation in this region. Mochizuki et al (2016) measured water-soluble organic nitrogen (WSON) and carbon in snow from a high elevation site in Japan. They find that WSON is closely connected to dust and pollution transported from the Asian continent.…”
Section: Regional Air Pollutionmentioning
confidence: 99%